Developments in the field of clinical allergy in 2018 through the eyes of Clinical and Experimental Allergy, Part II. Issue 12 (12th December 2019) - Roberts, Graham; Almqvist, C.; Boyle, R.; Crane, J.; Hogan, S. P.; Marsland, B.; Saglani, S.; Woodfolk, J. A.
Abstract: In this article, we describe developments in the field of clinical allergy as described by Clinical and Experimental Allergy in 2018; epidemiology, asthma and rhinitis, clinical allergy and allergens are all covered.